Causal associations between thyroid dysfunction and COVID-19 susceptibility and severity: A bidirectional Mendelian randomization study - Zhang, Zhihao; Fang, Tian; Lv, Yonggang (Frontiers in Endocrinology, 2022)
Background Observational studies have reported an association between Coronavirus disease 2019 (COVID-19) risk and thyroid dysfunction, but there is no clear causal relationship. We attempted to evaluate the association between thyroid function and COVID-19 risk using a bidirectional two-sample Mendelian randomization (MR) analysis. Methods Summary statistics of thyroid dysfunction (hypothyroidism and hyperthyroidism) traits were retrieved from ThyroidOmics Consortium. The genome‐wide association study (GWAS) statistics of COVID-19 susceptibility and its severity were taken from the COVID-19 Host Genetics Initiative, and the severity phenotype included hospitalized and very severe disease of COVID-19 participants. The inverse variance weighted (IVW) method was used as the main analysis, and the Weighted median (WM), MR-Egger and MRPRESSO methods were applied as supplements. The results were adjusted for the Bonferroni-corrected threshold. Results The forward MR estimates show that there was no effect of thyroid dysfunction on COVID-19 susceptibility and its severity. The reverse MR found that COVID-19 susceptibility was the suggestive risk factor for hypothyroidism (IVW: OR=1.577, 95%CI=1.065-2.333, P = 0.022; WM: OR=1.527, 95%CI=1.042-2.240, P = 0.029), and there was lightly association between COVID-19 hospitalized and hypothyroidism (IVW: OR=1.151, 95%CI=1.004-1.319, P = 0.042; WM: OR=1.197, 95%CI=1.023, 1.401, P = 0.023). There was no evidence supporting the association between any phenotype of COVID-19 and hyperthyroidism. Conclusion Our results identified that patients with COVID-19 susceptibility and its severity may be the suggestive risk factor for hypothyroidism, requiring further confirmation. Therefore, patients with sars-cov-2 infection should strengthen the monitoring of thyroid function.